Insight into Antioxidant Activity and Peptide Profile of Jinhua Ham Broth Peptides at Different Cooking Times - Ziyi Yang; Jiaming Cai; Evans Frimpong Boateng; Lujuan Xing; Wangang Zhang (MDPI AG, 2023)
This present study aimed to investigate the effects of various cooking times (1 h, 1.5 h, 2 h, 2.5 h, named as JHBP-1, JHBP-1.5, JHBP-2, JHBP-2.5) on the antioxidant activity and peptide profile of Jinhua ham broth peptides (JHBP). The peptides extracted from uncooked ham were used as an uncooked group with the name of JHBP-0. The results revealed that the antioxidant efficacy in the four cooked groups changed dramatically compared to JHBP-0. After cooking, the DPPH radical scavenging activity, hydroxyl radical scavenging activity and superoxide anion radical scavenging activity decreased, except for the Fe2+ chelation and ABTS+ scavenging capacity which increased significantly. However, the cooked groups still showed a strong antioxidant capacity. In particular, the superoxide anion radical scavenging ability and the Fe2+ chelation action were significantly stronger compared to glutathione (GSH) and butylated hydroxytoluene (BHT) (p < 0.05). JHBP-1.5 also displayed stronger antioxidant capacity than the other three cooked groups, and its secondary structure and mass distribution changed significantly after cooking, specifically with an increased proportion of helix and <1 kDa peptides. Moreover, the constitution of free amino acids (FAAs) and the types of peptides released in the broth increased significantly with a longer cooking time. In total, 1306 (JHBP-0), 1352 (JHBP-1), 1431 (JHBP-1.5), 1500 (JHBP-2), and 1556 (JHBP-2.5) peptide sequences were detected using LC-MC/MC. The proportion of <1 kDa peptides also gradually increased as the cooking time extended, which is consistent with the molecular weight distribution measurements.